Noninvasive determination of atrial fibrillation cycle length by atrial colour tissue Doppler imaging in horses. (30th August 2013) - Decloedt, A.; de, D.; van der, N.; Verheyen, T.; van, G.
Summary Reasons for performing study Atrial fibrillation cycle length (AFCL) is an indicator of atrial electrical remodelling during atrial fibrillation (AF). Objectives To compare AFCL measured invasively from an intra‐atrial electrogram (AFCLEGM) with AFCL measured noninvasively by atrial colour tissue Doppler imaging (AFCLTDI). Study design Prospective descriptive clinical study. Methods Measurements were performed in 31 episodes of AF or flutter in 29 horses (588 ± 61 kg bwt, 9 ± 3 years old) admitted for transvenous electrical cardioversion. The AFCLEGM was measured from an intracardiac electrogram using a bipolar sensing/pacing electrode inserted into the right atrium. The AFCLTDI was measured from atrial colour tissue velocity curves in the following 5 regions: 1) left atrial free wall from a right parasternal 4‐chamber view, 2) left atrial free wall from a short‐axis view, 3) left atrial free wall from a left parasternal long‐axis view, 4) interatrial septum, and 5) right atrial dorsal wall near the tuberculum intervenosum. The AFCLEGM and AFCLTDI from the 5 regions were compared using a one‐way repeated‐measures ANOVA with Bonferroni correction for multiple comparisons and calculation of the Bland‐Altman mean bias and limits of agreement of AFCLEGM and AFCLTDI. Results The AFCLEGM was 161 ± 18 ms in 29 AF episodes. Two horses showed atrial flutter and had an AFCLEGM of 244 and 324 ms. The mean bias between AFCLTDI and AFCLEGM ranged from ‐18 to +9 ms depending on the atrial wall region. The AFCLTDI was significantly shorter in the left atrial free wall from the right parasternal 4‐chamber view and short‐axis view than in the other regions (P<0.001). Conclusions Tissue Doppler imaging allows noninvasive measurement of AFCL in horses with AF and is able to identify spatial differences within the equine atria. Atrial fibrillation cycle length is an indicator of atrial electrical remodelling and is an important parameter to study AF pathophysiology or the effect of antiarrhythmic drugs.